Breeding Soundness Evaluation in Bulls: A Comprehensive Review - Javkhlan, Ariuntungalag (Mongolian Journal of Agricultural Sciences, 2023)
Breeding soundness evaluation (BSE) is a crucial process that assesses the reproductive potential of bulls intended for use as herd sires. This comprehensive method involves a thorough examination of the bull's physical health, reproductive organs, and semen quality, including overall examination, scrotal assessment, and semen evaluation. Among these components, precise semen evaluation is the most critical part of BSE. This method is reliable, cost-effective, and economically prudent for assessing the potential fertility of sire bulls. In this review, the information and application of BSE in bulls was summarized. Furthermore, knowledge gained from the reproductive biology of domestic animal species can be utilized through these BSE guidelines to study and develop assisted reproductive technologies, serving as tools for the ex-situ gene conservation of endangered wild animals such as argali sheep, yak, reindeer, and Przewalski horses—species that are vital members of Mongolia's wild fauna.